Reasons for Engagement: SME Owner-Manager Motivations for Engaging in a Workplace Mental Health and Wellbeing Intervention. Issue 10 (October 2018) - Dawkins, Sarah; Martin, Angela; Kilpatrick, Michelle; Scott, Jenn
Abstract : Objective: Small-to-medium enterprises (SMEs) require specialized attention regarding workplace mental health (WMH), but can be challenging to engage in WMH promotion interventions. This cross-sectional study analyzed self-reported motivations of SME owner/managers who engaged in a WMH promotion intervention specifically designed for SMEs. Methods: Data from 297 SME owner/managers was thematically coded before conducting multinominal logistical regression analyses to determine reasons for engagement based on a series of predictors, including owner/manager psychological distress, recent experience of a stressful work event, and business confidence. Results: Owner/manager psychological distress, experience of a recent stressful workplace, and low 12-month business confidence incident were important predictors of engagement. Conclusion: The findings provide important insights into the uptake of a WMH promotion intervention, which can inform the design and future recruitment strategies for WMH promotion interventions within the SME sector.